The correlation between heavy metal ions in blood and metabolic dysfunction-associated steatotic liver disease from 1999 to 2018 based on NHANES data - Ma, Haijun; Zhao, Ju; Xu, Jian (Frontiers in Public Health, 2025)
BackgroundMetabolic-associated steatohepatitis and liver fibrosis (MASLD) is a growing public health concern, with environmental factors potentially playing a role in its development. This study aimed to investigate the associations between serum cadmium and mercury levels and the risk of MASLD in a nationally representative sample from the United States.MethodsData from the National Health and Nutrition Examination Survey from 1999 to 2018 were analyzed. Serum cadmium and mercury concentrations were measured, and MASLD was defined based on established criteria. Logistic regression models were used to assess the associations between serum metal levels and MASLD, with adjustments for potential confounders. Stratified analyses and restricted cubic spline curves were employed to examine subgroup differences and nonlinear relationships.ResultsThe study revealed significant inverse associations between serum cadmium and mercury levels and the likelihood of MASLD. Individuals in the highest quartiles of cadmium and mercury had lower odds of MASLD compared to those in the lowest quartiles (Model 3: Cadmium Q4 vs. Q1, Mercury Q4 vs. Q1). Stratified analyses showed stronger inverse associations in older adults, males, and never smokers for cadmium, and in females and individuals without diabetes for mercury. Nonlinear dose–response curves indicated critical thresholds beyond which the risk dynamics changed.ConclusionHigher serum levels of cadmium and mercury were associated with a lower risk of MASLD, with notable variations across subgroups. These findings challenge the conventional understanding of these heavy metals as universally harmful and highlight the need for further research to unravel the complex interplay between environmental exposures and MASLD pathophysiology.